Analysis of Legal Protection of Consumers through Halal Certification on Medicinal Products - Mubarak, Haikal; Miliyandra, Miliyandra; Priyanto, Eka; Respati, Gilang; Wiradirja, Imas Rosidawati (Formosa Journal of Applied Sciences, 2025)
This study aims to analyze the legal protection of consumers through halal certification, especially in the pharmaceutical industry. By using a qualitative approach and analyzing secondary data, this study tries to understand how halal certification can increase consumer confidence in pharmaceutical products and provide assurance of the safety and quality of the products they consume. However, in implementing halal certification in the pharmaceutical industry, there are several challenges that need to be overcome. From complex regulations to high certification costs, all of these can be barriers for pharmaceutical manufacturers to obtain halal certification for their products. Therefore, it is important to continue to research and improve the halal certification system in order to provide maximum protection for consumers.